Thermophysiological Comfort Behaviour of Cut Protective Workwear Consisting of Filament Twisted Multicomponent Hybrid Yarn - Zayedul Hasan; Rochak Rathour; Apurba Das; Ramasamy Alagirusamy; Nandan Kumar (Tekstilec, 2024)
Current cut protective gear is subject to several difficulties, such as the use of heavy fabric, complicated donning processes, lack of comfort and limited movement. When selecting the most comfortable cut protective fabric, it is important to consider the end users' specific needs. The aim of this study was to enhance the comprehension and optimisation of protective apparel for superior occupational safety and protection by exploring the intricate link between material composition, yarn structure and comfort parameters. Various combinations of filament twisted core sheath yarn consisting of stainless-steel/glass with high-performance polyethylene and polyester wraps were used to fabricate thermo-physiological comfortable cut protective workwear fabric. Twelve cut protective fabrics with the same areal density (200 g/m2) were prepared with 6-end satin weave using filament twisted core sheath yarn of five distinct linear densities (98.4 tex, 73.8 tex, 59.1 tex, 49.2 tex and 39.4 tex). These fabric samples were used to evaluate thermophysiological characteristics, including air permeability, dry and evaporative heat resistance, thermal conductivity, moisture permeability, wettability and moisture wicking according to the established standard. The cut protection of each sample was also measured according to EN 13997. The cut protection and thermo-physiological comfort attributes of cut-resistant clothing are greatly influenced by the proportion of core material (stainless-steel/glass) and yarn structural parameters (linear density and twist direction), which was observed by analysing the results. An increased core material percentage (stainless-steel/glass) contributes to increased fabric thickness and reduced bulk density, which influences the thermophysiological comfort attributes of the developed cut protective workwear fabric. Fabric made from a higher proportion of core material (stainless-steel/glass) with a lower bulk density exhibited an acceptable cut protection level and performed better in terms of thermo-physiological comfort attributes.